SWOT Analysis of AI Integration in Islamic Education: Cognitive, Affective, and Psychomotor Impacts - Andri Nirwana AN; Alfan Rifai; Mohamad Ali; Triono Ali Mustofa; Viky Nur Vambudi; Muh. Nur Rochim Maksum; Mush'ab Umar Budihargo (Qubahan Academic Journal)
Artificial Intelligence (AI) has emerged as a transformative force in education, including Islamic religious education, where it offers new opportunities to enhance learning methodologies. This study aims to analyze the integration of AI in Islamic education by evaluating its strengths, weaknesses, opportunities, and threats (SWOT analysis) while categorizing its impact on cognitive, affective, and psychomotor domains based on Bloom’s Taxonomy. A qualitative approach using library research methodology was employed, with data collected from academic journals, books, and research reports, analyzed through a SWOT framework. The findings indicate that AI significantly enhances cognitive and psychomotor learning in Islamic education. AI-based tools, such as ClassPoint AI, AI Chatbots, and Squirrel AI, contribute to knowledge retention, adaptive learning, and skill-based training in areas like Quranic recitation, prayer practices, and Islamic jurisprudence. However, AI remains limited in fostering affective learning, as it lacks human emotional intelligence and the ability to provide moral and ethical guidance, which are essential in Islamic education. The study also reveals challenges such as ethical concerns, technological disparities, and socio-cultural resistance in integrating AI into religious studies. Despite these limitations, AI presents significant opportunities, particularly in remote learning, personalized education, and accessibility for underserved communities. This research provides a structured evaluation of AI’s role within Bloom’s Taxonomy, offering insights into AI’s potential and limitations in Islamic education. The study contributes theoretically by linking AI-driven education with pedagogical principles, while practically, it guides educators and policymakers in strategically implementing AI while preserving Islamic ethical values. The study concludes that while AI enhances knowledge acquisition and skill-based learning, human educators remain essential for moral and ethical development. Future research should focus on developing ethical AI models, hybrid AI-human teaching approaches, and AI-driven affective learning systems to bridge gaps in AI-assisted moral and spiritual education.